Regional Economic Security in the Context of Budget System Stability - Anatolyevna Efremova, Lyudmila; Ivanovna Lazareva, Galina; Antsasovna Rusetskaya, Elvira; Sergeevich Molchan, Alexey; Petrovna Anufriyeva, Anna (International Journal of Engineering and Technology, 2018)
The present-day state finances condition demonstrates the need for specifying methodological and practical aspects of providing budget system financial stability. The objectives of overcoming the budget deficit at all levels set by the Russian Federation government are aimed at creating the necessary conditions for providing the regionâ€™s financial security as a key functional component of its economic security.The materials presented in the article provide characteristics of Stavropol Krai and Krasnodar Krai budgets, which were obtained by the authors as a result of the analysis of the basic medium-term development programs of the given regions. The possible use of budget policies indicators and instruments for the assessment of economic security and financial stability of a federal subject of Russia is indicated. The article investigates the opportunity to assess regional economic security based on the study of socio-economic parameters of its development and on the application of the system analysis methods to major indicators of a federal subject of Russia financial and budget policies.The elements of scientific novelty are determined by the fact that the article substantiates the necessity to develop a complex of measures for improving the forms and methods of the state financial support for regions with the mandatory inclusion of activities aimed at increasing regional economic security.Â